Degree of Achievability of Omnidirectional Motion in Various Mobile Robot Designs: A Review - Ajju Raja Justus (IAES International Journal of Robotics and Automation (IJRA), 2016)
In the current field of robotics, many new robots are being developed based on different working principles. Each robot has its own strengths and weaknesses. Omnidirectional mobility is a major functional requirement for performing more complex actions. This article is a comprehensive study of some of the robots developed by different people with distinctive driving mechanisms. The actuation, driving method, operating conditions and control mechanism of all the selected robots is studied. Then finally, all the considered robots are compared based on various parameters to gauge the efficiency and degree of achievability of omnidirectional motion in each robot. Therefore, by the end of this article, we can have an understanding of how much effective each driving mechanism is in producing omnidirectional mobility.